An Analysis of Derivational Process in Batak Toba Language Based on the Song “Anakkonhi Do Hamoraon Di Ahu” by Nahum Situmorang - Purba, Christian Neni; Gaol, Daniel Binsah Lumban; Irwansyah, Syalaisha Syafira; Sinaga, Venyta (Innovative: Journal Of Social Science Research, 2025)
This study examines the derivational processes in the Batak Toba song entitled “Anakkonhi Do Hamoraon Di Ahu” focusing on how affixes shape new words and influence their grammatical and semantic properties. The research aims to identify and classify the derivational morphemes such as prefixes, suffixes, and confixes used in the lyrics and determine their impact on word formation and meaning. A descriptive qualitative method is employed to analyze data extracted from the song’s lyrics. The study also highlights the cultural significance of these derivational processes in conveying the song’s thematic messages. This research contributes to a deeper understanding of morphological structures in Batak Toba and their role in traditional music.